4=6u-3

Rewrite the equation as 6u-3=4.

6u-3=4

Multiply each term by u-3 and simplify.

Multiply each term in 6u-3=4 by u-3.

6u-3⋅(u-3)=4⋅(u-3)

Cancel the common factor of u-3.

Cancel the common factor.

6u-3⋅(u-3)=4⋅(u-3)

Rewrite the expression.

6=4⋅(u-3)

6=4⋅(u-3)

Simplify 4⋅(u-3).

Apply the distributive property.

6=4u+4⋅-3

Multiply 4 by -3.

6=4u-12

6=4u-12

6=4u-12

Rewrite the equation as 4u-12=6.

4u-12=6

Move all terms not containing u to the right side of the equation.

Add 12 to both sides of the equation.

4u=6+12

Add 6 and 12.

4u=18

4u=18

Divide each term by 4 and simplify.

Divide each term in 4u=18 by 4.

4u4=184

Cancel the common factor of 4.

Cancel the common factor.

4u4=184

Divide u by 1.

u=184

u=184

Cancel the common factor of 18 and 4.

Factor 2 out of 18.

u=2(9)4

Cancel the common factors.

Factor 2 out of 4.

u=2⋅92⋅2

Cancel the common factor.

u=2⋅92⋅2

Rewrite the expression.

u=92

u=92

u=92

u=92

u=92

The result can be shown in multiple forms.

Exact Form:

u=92

Decimal Form:

u=4.5

Mixed Number Form:

u=412

Solve for u 4=6/(u-3)